Loss of DJ-1 alleviates microglia-mediated neuroinflammation in Parkinson’s disease via autophagy-lysosomal degradation of NLRP3 - Miao, Qianqian; Wang, Tiantian; Wang, Haoran; Yu, Yanxia; Jin, Xing (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the role and underlying mechanism of DJ-1 in regulating NLRP3 inflammasome-mediated neuroinflammation during Parkinson’s disease.MethodsWe used LPS to stimulate primary microglia in vitro and performed stereotactic injection of LPS into the substantia nigra of mice in vivo to investigate changes in DJ-1 expression following inflammatory stimulation. To evaluate the functional effects of DJ-1 on NLRP3 inflammasome activation, we used siRNA to knock down DJ-1 in primary microglia or BMDMs and analyzed downstream inflammatory responses as well as the specificity of this regulation. In vivo, we used microglia-specific AAV to selectively silence DJ-1 in the substantia nigra to further evaluate the anti-inflammatory effect of DJ-1 deficiency. To validate the direct interaction between DJ-1 and NLRP3, we performed co-immunoprecipitation and proximity ligation assay. We used the autophagy inhibitor 3-MA and activator rapamycin to investigate how NLRP3 is degraded upon DJ-1 deficiency in CRISPR-Cas9-engineered DJ-1 knockout HEK-293 cells.ResultsDJ-1 were significantly upregulated following LPS or LPS plus ATP stimulation in primary microglia. Similarly, after stereotactic LPS injection into the substantia nigra, we observed a significant upregulation of DJ-1 expression. Knockdown of microglial DJ-1 markedly suppressed NLRP3 inflammasome activation, as evidenced by reduced mature caspase-1 and decreased IL-1β secretion. We confirmed this phenomenon in BMDM and found that DJ-1 knockdown specifically inhibited NLRP3 inflammasome activation, with no effect on NLRC4 or AIM2 inflammasomes. In vivo, microglia-specific DJ-1 knockdown significantly attenuated microglial NLRP3 inflammasome activation in the substantia nigra and exerted neuroprotective effects after LPS treatment. Furthermore, DJ-1 was found to directly bind NLRP3 and stabilize its conformation, thereby preventing autophagic degradation.ConclusionThis study demonstrates that DJ-1 deficiency in microglia inhibits NLRP3-driven inflammation by promoting NLRP3 degradation through the autophagy-lysosome pathway. Future studies should focus on identifying the specific binding sites and structure of DJ-1 with NLRP3, as well as investigating whether inhibiting DJ-1 in microglia could serve as a potential therapeutic target for suppressing neuroinflammation in Parkinson’s disease.